Representations of digital violence against women in cartoons on digital platforms "An analytical study of the Tomato Cartoon page on Facebook and Instagram from November 30, 2018 to December 2, 2024 (Abhat Journal, 2025)
The primary objective of the study is a semiotic analysis of representations of digital violence against women in cartoons published on Facebook and Instagram. This study is a descriptive study that relies on content analysis to understand representations of digital violence against women within digital cartoons. The study population consisted of cartoons published on the Tomato Cartoon page, the Arab cartoon platform, on Facebook and Instagram during the period from November 30, 2018 to December 2, 2024. These cartoons addressed topics related to digital violence against women. Cartoons were used as the primary unit of analysis, and a semiotic analysis card was designed in light of Roland Barthes' theory. The researcher relied on a deliberate sample consisting of approximately (23) cartoons collected from the Tomato Cartoon account on Facebook and Instagram. The study men appeared in all cartoons as a direct or indirect source of violence.  Moreover, they were depicted as executioners, oppressors, controllers, or indifferent spectators. The drawings used rich visual symbols such as the gallows, knife, electric chair, closed curtain, rope, severed head, and shackles. These symbols suggest dimensions of death, oppression, siege, and symbolic death. The study recommends organizing campaigns to raise awareness in the society about violence against women and children and ways to address these issues
Keywords: Representations; Digital Violence; Women; Cartoons; Digital Platforms